Teacher ideologies of English in 21st century Norway and new directions for locally tailored ELT. (November 2020) - Chvala, Lynell
Abstract: English language education is designed to prepare learners for the needs of the world today and in the future. This article explores Norwegian teachers' ideologies of English in society and English in school to consider locally relevant 21st century English language teaching (ELT). Language ideologies construct certain social realities that shape teachers' understanding of English and contextually meaningful ELT. Data was generated through extensive interviews with 12 teachers in basic education in Norway. Data were inductively analyzed using methods from grounded theory and resulted in a conceptual framework of teacher ideologies. Findings reveal English as a natural, supranational language in modern Norwegian society, but also as personal and threatening. English in school, on the other hand, is foreign, communicative, historic and cultural, humanistic, for learning interdisciplinary content, and in flux . The final category explores self-reflexive questions teachers raise about ownership and identity, diversity, digitalization, and global orientation. In considering new directions, findings suggest the need for a metalanguage for English in non-native contexts that better encompasses experiences in an increasingly diverse and interconnected world. A current initiative to support teachers in exploring new and locally appropriate directions in ELT is then recommended.